DINAMIKA PENCATATAN PERKAWINAN DALAM PERSPEKTIF HUKUM KEKELUARGAAN DI INDONESIA DAN PEMBARUAN HUKUM ISLAM - Birbik, M. Hafil (International Conference on Humanity Education and Society (ICHES), 2024)
Marriage registration is one of the family law reformation carried out by muslim countries in the world. The aim is to achieve legal certainly, rule of law, and legal protections of a marriage. Hence, various contries in the Islamic world made the registration of marriage as on oligation which regalized in any regulatory. However, in itsimplementation, there is a difference perspective requirements and not related to the validity of the marriage because in this case validity of the marriage remained propped against the provisions of islmic law. Marriage registration is one of the national legal principles under Law Number 1 of 1974 on marriage. In Indonesia marriage legislation, the existence of marriage registration related to and devined validity of marriage besides following provision of their religions and beliefs. Otherwise registration and making marriage acte is an obligation in marriage legislation in Indonesia. But in the practice, registration and making marriage acte is ambiguity, because that obligation only administratively, not influence to marriage validity. Even the marriage done based on their religion provision, but if not registrate, the marriage does not have legal position. This unregistrative marriage cause husband, wife and ther children do not have legal protection. Relation with that, its need legal reform related to marriage regislation with constectual approach for giving legal certainly and protection for husband, wife and their children.